Do Good Carefully: The Long-Term Effects of DDT Exposure in Early Childhood on Education and Employment - Simon Chang; Kamhon Kan (Institute of Labor Economics (IZA), 2022)
For decades, the debate on using DDT to control malaria has focused on the balance between immediate public health gains and ecological costs, ignoring DDT's long-term harmful effects on humans. Using data from the large-scale indoor residual spraying of DDT that took place in Taiwan in the 1950s, we estimate the long-term effects of DDT exposure in early childhood on education and employment in adulthood. Our identification hinges on the unexpected extension of DDT spraying even after malaria had already been largely brought under control. Our finding shows that DDT exposure in early childhood is associated with less education and worse employment in adulthood. However, the dose-response curves are non-linear.
Keywords: I1; Q5; 330; DDT; endocrine-disrupting chemicals; malaria; human capital; Taiwan